2022
DOI: 10.3390/ijerph192416678
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Skin Homeostasis Changes after Using Different Types of Excipients in Healthy Individuals

Abstract: Excipients are used as vehicles for topical treatments; however, there are not many studies that evaluate the impact of different excipients themselves. The aim of this research is to assess skin homeostasis changes in healthy individuals after using water/oil (W/O), oil/water (O/W), Beeler base, foam and Vaseline excipients. A within-person randomized trial was conducted that included healthy individuals without previous skin diseases. Skin barrier function parameters, including stratum corneum hydration (SCH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Vaseline also strongly modulates antimicrobial action and helps the skin barrier in blocking invading pathogens (Czarnowicki et al, 2015). According to Ordonez-Toro et al (2022), vaseline can reduce erythema. Maarouf et al (2019), also suggested the use of vaseline to improve the skin barrier and erythema.…”
Section: Observation Of Skin Anatomy Pathologymentioning
confidence: 99%
“…Vaseline also strongly modulates antimicrobial action and helps the skin barrier in blocking invading pathogens (Czarnowicki et al, 2015). According to Ordonez-Toro et al (2022), vaseline can reduce erythema. Maarouf et al (2019), also suggested the use of vaseline to improve the skin barrier and erythema.…”
Section: Observation Of Skin Anatomy Pathologymentioning
confidence: 99%
“…Likewise, external damage such as the use of personal protective equipment [13] or sun exposure [14] affects these skin biophysical parameters. Also, the excipients used for topical treatments have a distinct impact on the barrier function of the skin [15]. However, there is significant variation in skin properties for different ages, genders and body regions due to the differences in the structure and morphology of the skin tissues [16].…”
Section: Introductionmentioning
confidence: 99%